EXPLORATION OF FACTORS INFLUENCING CONSUMER PREFERENCES IN PRODUCT SELECTION: A MASLAHAH PERSPECTIVE - Ismail; Salisa Amini; Isnaini Harahap; Muhammad Ridwan (ITB AAS Indonesia Surakarta, 2026)
Maslahah, a fundamental concept in Islamic economics, emphasizes on general welfare and mutual benefit. This article explores the factors that influence Muslim consumers' preferences in their daily product selection from the perspective of maslahah. The approach carried out is content analysis by examining 10 relevant studies related to consumer preferences. The main factors found include product attributes, price, quality, and religious values such as halal awareness and halal labeling. The results of the study show that consumer preferences are not only driven by material factors such as price and quality, but also influenced by spiritual and social factors related to sharia principles. Muslim consumers tend to be more selective in their product selection, ensuring that the products they choose are in accordance with halal and thayyib (good and beneficial) principles. The implementation of the maslahah concept includes a balance between personal benefits and social and environmental benefits. The study also found that while halal labels are recognized as an important element, other factors such as price, ease of access, and trust in the manufacturer also have an influence on purchasing decisions. Muslim consumers tend to consider more than just the halalness of the product, but also the convenience and comfort in daily use. Muslim consumer preferences reflect the close link between material needs and religious demands. This article also provides important insights for the development of products and services that are in line with the principles of maslahah in Islamic economics.